Cu(II) AND Cd(II) COORDINATION POLYMERS DERIVED FROM PYRAZINE-2,3-DICARBOXYLATO AND 1-VINYLIMIDAZOLE LIGANDS: SYNTHESIS, CHARACTERIZATION AND HYDROGEN STORAGE CAPACITIES - Gorduk, Semih; Yilmaz, Hakan; Andac, Omer (SOC CHEMISTS TECHNOLOGISTS MADECONIA, 2019)
In this study, two new coordination polymers of Cu(II) and Cd(II) ions with pyrazine-2,3-dicarboxylic acid and 1-vinylimidazole were synthesized. The structures of these coordination polymers were characterized with elemental analysis, infrared spectroscopy, thermal analysis, powder X-ray diffraction, and magnetic susceptibility techniques. According to the results of the thermal analysis, the coordination polymers that contained water molecules decomposed below 100 degrees C, and the final products for both coordination polymers were the related metal oxides in an oxygen atmosphere. Powder X-ray diffraction analysis revealed that the coordination polymers were in the crystalline form. The hydrogen storage capacities and surface areas of the coordination polymers were also determined. The highest hydrogen storage capacities were measured as 296 ml/g for the Cu(II) coordination polymer and 330 ml/g for the Cd(II) coordination polymer at approximately 75 bar and 75 K.
Keywords: pyrazine-2,3-dicarboxylato; 1-vinylimidazole; coordination polymer; hydrogen storage; bridging ligand; METAL-ORGANIC FRAMEWORKS; N-DONOR LIGANDS; CRYSTAL-STRUCTURES; MAGNETIC-PROPERTIES; SQUARIC ACID; COMPLEXES; SORPTION; ADSORPTION; IMIDAZOLE; SERIES; Chemistry; Engineering